Implementasi Program Sekolah Penggerak dalam Kebijakan Pendidikan Merdeka Belajar (Studi di Sekolah Dasar Kecamatan Montong Gading Lombok Timur) - Masdin Nurhayani; Masdin Abdul Hafiz (Schemata: Jurnal Pascasarjana UIN Mataram, 2024)
The Sekolah Penggerak is a school that focuses on developing student learning outcomes holistically by realizing the profile of Pancasila Students which includes competencies and characters that begin with superior human resources (principals and teachers). This study aims to determine the Implementation of the Driving School Program in Merdeka Belajar Education Policy. This research uses a descriptive qualitative approach. Data collection techniques are observation, interviews and documentation. While the data analysis technique uses an interactive model, namely data reduction, data presentation, discussion and conclusions. The result of the research is that the implementation of driving schools in elementary schools in Montong Gading sub-district, East Lombok, is carried out in accordance with the 5 interventions programmed by the government. The implementation process of these schools has similarities, namely in consultative and asymmetrical assistance programs, strengthening school human resources and data-based planning. In addition, each school also has different programs related to the new paradigm teaching intervention and school digitalization, because schools can create programs according to the needs of human resources and consider the needs of students. Keywords: Merdeka Belajar, Sekolah Penggerak Sekolah Penggerak merupakan sekolah yang berfokus pada pengembangan hasil belajar siswa secara holistik dengan mewujudkan profil Pelajar Pancasila yang mencakup kompetensi dan karakter yang diawali dengan SDM yang unggul (kepala sekolah dan guru). Penelitian ini bertujuan untuk mengetahui Implementasi Program Sekolah Penggerak dalam Kebijakan Pendidikan Merdeka Belajar. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif. Teknik pengumpulan data adalah dengan observasi, wawancara dan dokumentasi. Sedangkan teknik analisis data menggunakan model interaktif yaitu reduksi data, sajian data, pembahasan dan kesimpulan. Hasil penelitian adalah bahwa implementasi sekolah penggerak di Sekolah Dasar Kecamatan Montong Gading Lombok Timur dilaksanakan sesuai dengan 5 intervensi yang diprogramkan oleh pemerintah. Proses pelaksanaan dari sekolah-sekolah tersebut memiliki persamaan yaitu pada program pendampingan konsultatif dan asimetris, penguatan SDM sekolah dan perencanaan berbasis data. Disamping itu, setiap sekolah juga memiliki program yang berbeda terkait intervensi pembalajaran paradigma baru dan digitalisasi sekolah, karena sekolah dapat membuat program sesuai dengan kebutuhan SDM dan mempertimbangkan kebutuhan peserta didik. Kata kunci: Merdeka Belajar, Sekolah Penggerak